2019
DOI: 10.3390/c6010001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic Characterization and Photoactivity of Zr(IV) Phthalocyanines Functionalized with Aminobenzoic Acids and Their GO-Based Composites

Abstract: Two complexes of bis(aminobenzoato)zirconium(IV) phthalocyanine and their graphite oxide-based composites were synthesized and characterized in respect of their photochemical properties. Structures of phthalocyanines were confirmed by Mass and infrared spectroscopies. The absorption and photoluminescence spectra were investigated to show various behavior of the complexes in different media (dimethyl sulfoxide and saline). Optical technique (monitoring variation of absorption spectra of diphenylisobenzofuran us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…S3 and S4 in Supplementary Information). Other identified signals are at m/z = 899.26 for PcZr(ASA) and m/z = 928.74 for PcZr(APhA)-their presence indicates that two solvent molecules (DMF) enter the coordinating sphere of zirconium, which confirms our earlier research on complexes of axially substituted zirconium phthalocyanines (Tahershamsi et al 2020;Tretyakova 2007). Fragmentation of the complex takes place in the following mode: in the first stage, the axial ligand is disconnected and a PcZrO 2 complex is formed with m/z = 637.78, followed by demetallation of the complex confirmed by the presence of the signal of free phthalocyanine at m/z = 515.82.…”
Section: Mass Spectroscopy (Esi-ms)supporting
confidence: 85%
See 3 more Smart Citations
“…S3 and S4 in Supplementary Information). Other identified signals are at m/z = 899.26 for PcZr(ASA) and m/z = 928.74 for PcZr(APhA)-their presence indicates that two solvent molecules (DMF) enter the coordinating sphere of zirconium, which confirms our earlier research on complexes of axially substituted zirconium phthalocyanines (Tahershamsi et al 2020;Tretyakova 2007). Fragmentation of the complex takes place in the following mode: in the first stage, the axial ligand is disconnected and a PcZrO 2 complex is formed with m/z = 637.78, followed by demetallation of the complex confirmed by the presence of the signal of free phthalocyanine at m/z = 515.82.…”
Section: Mass Spectroscopy (Esi-ms)supporting
confidence: 85%
“…Admittedly, agglomeration is observed at quite high concentrations (above 10 -4 M), but it does occur. It is interesting that for PcZr(ASA), and for none of the previously studied complexes (Tahershamsi et al 2020;Gerasymchuk et al 2004;Tomachynski et al 2008;Tretyakova et al 2007), agglomeration in DMSO was not observed in a much wider range of concentrations. It is associated, in our opinion, with the nature of the axial ligand, which, in contrast to those previously studied, has more hydrophobic character.…”
Section: Uv-vis-nir Absorbance Measurementsmentioning
confidence: 90%
See 2 more Smart Citations
“…The following samples described in detail previously [ 9 , 29 , 44 , 45 ] were tested in this study: pure graphite oxide (GO), GO-PcZr(Lys) 2 -Ag (0.5 g/10 mL) (IV), GO-Ag (0.5 g/10 mL) (V), and GO-PcZr(Lys) 2 (VI). A brief scheme of composites preparation is shown in Figure 9 .…”
Section: Methodsmentioning
confidence: 99%